1987
DOI: 10.1007/bf00176478
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of quazepam and triazolam on cognitive-neuromotor performance

Abstract: The pharmacological activity of quazepam, a BZ1 specific benzodiazepine, was compared to the effects of triazolam, a BZ1, BZ2 nonspecific benzodiazepine. Using a double-blind procedure, single oral doses of quazepam (15 or 30 mg), triazolam (0.5 or 1.0 mg) and placebo were administered to 21 healthy young men according to a random Latin square design balanced for order of drug administration. The drug effects on the performance of motor coordination and cognitive tasks were monitored for 7 h following drug ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
(23 reference statements)
2
11
0
Order By: Relevance
“…As for CPT, no significant between‐drug differences were observed. In previous studies assessing the acute effects of benzodiazepines on psychomotor performance, it was demonstrated that the time course of the impairment profiles was not concordant with the pharmacokinetic findings 20,32 . In particular, the peak latency of the psychomotor impairment occurred much earlier than that expected by the pharmacokinetic data published for quazepam; that is, <2 h 20 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As for CPT, no significant between‐drug differences were observed. In previous studies assessing the acute effects of benzodiazepines on psychomotor performance, it was demonstrated that the time course of the impairment profiles was not concordant with the pharmacokinetic findings 20,32 . In particular, the peak latency of the psychomotor impairment occurred much earlier than that expected by the pharmacokinetic data published for quazepam; that is, <2 h 20 .…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies assessing the acute effects of benzodiazepines on psychomotor performance, it was demonstrated that the time course of the impairment profiles was not concordant with the pharmacokinetic findings 20,32 . In particular, the peak latency of the psychomotor impairment occurred much earlier than that expected by the pharmacokinetic data published for quazepam; that is, <2 h 20 . The high lipophilicity profiles of the bezodiazepines adopted in the present study may well lead to a short duration of clinical action despite their various elimination half‐lives, resulting in a lack of prominent hangover effects on CPT indices.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Choice reaction time seems to be sensitive to the effects of benzodiazepines under the same types of conditions seen with simple reaction time tests. Those studies that evaluate the effects of a benzodiazepine within the time frame of the half-life of a therapeutic dose of the parent compound typically detect impairment with these tests (Nikaido & Ellinwood, 1987;Preston et al, 1988;Roache & Griffiths, 1987;Seppala et al, 1976;Subhan et al, 1986;Warot et al, 1987). In a study by Schaffler & Klausnitzer (1989) impairment was noted with a subchronic dose of bromazepam over a 7 day period but in a study by Preston et al (1988) subtherapeutic doses of lorazepam did not impair choice reaction time performance.…”
Section: Reaction Timementioning
confidence: 99%
“…Sinusoidal patterns are commonly used and the performance measurement is usually the subjects deviation from the generated wave summed over the entire test pattern. Tracking tasks, like reaction time tests, evaluate skills that are affected by hypnotic doses of benzodiazepines only a short period of time after administration (Nikaido & Ellinwood, 1987;Linnoila et al, 1990;Stoller et al, 1976;Subhan et al, 1976). In many studies a reduction in tracking ability was observed 2 to 4 h after drug administration but not the morning following either a single dose or a number of consecutive evenings administration of the same dose (Erwin et al, 1986;Fisch et al, 1990;Laurell & Tornros, 1986;Linnoila et al, 1981;Mattila, 1988;Mattila et al, 1988b;Nicholson, 1979Nicholson, , 1986.…”
Section: Trackingmentioning
confidence: 99%